Kualitas Pelatihan dan Pendidikan Maritim dari Sudut Pandang Taruna dan Perwira Siswa - Agus Hadi Purwantomo; Rahyono; Dian Wahyu Hidayat; Rahul Sukhanna (Politeknik Ilmu Pelayaran Semarang, 2021)
The world Maritime Education and Training Institute (PPM) under the International Maritime Organization (IMO) plays an important role in producing ideally skilled and competent seafarers. Developing countries, especially Indonesia, are challenged to be able to improve the quality of PPM institutions in developing their competencies that are globally oriented and based on a high level of excellence, so as to be able to maintain industrial competitiveness and overcome further globalization which causes economic growth in developing countries. This type of research uses descriptive research with a structured interview method. The main objective of this study is to assess the quality of maritime education and training from the perspective of seafarers in Indonesia. The result of this research found that a national strategy was needed for professional development for the cognitive development of seafarers.